Understanding global warming with Max Axiom, super scientist - Biskup, Agnieszka (Graphic library. Graphic science., 2008)
Max Axiom teaches the science behind global warming, traveling the world to explore global warming, deforestation, the polar ice sheets, and solutions to climate change.